Seminar on Stochastic Analysis, Random Fields and Applications IV 2004
DOI: 10.1007/978-3-0348-7943-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Resonance: A Comparative Study of Two-State Models

Abstract: Abstract. We consider a dynamical system describing the motion of a particle in a double well potential with a periodic perturbation of very small frequency, and an additive stochastic perturbation of amplitude ε. It is in stochastic resonance if the solution trajectories amplify the small periodic perturbation in a 'best possible way'. Systems of this type first appeared in simple energy balance models designed for a qualitative explanation of global glacial cycles. Large deviations theory provides a lower bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As mentioned above in leading order the transitions of the diffusion process X t between the wells can be approximated by a two state Markov Chain Y t = ±1 which have been studied [46,47,48,42]. Further comparative studies of the stochastic resonance for the diffusion case X t versus the Markov Chain Y t case were done by Hermann, Imkeller, Pavlyukevich and Peithmann in [49,50,51,52]. A collection of papers on comparative studies between stochastic resonance in diffusion and Markov Chains can be found in the monograph [42].…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…As mentioned above in leading order the transitions of the diffusion process X t between the wells can be approximated by a two state Markov Chain Y t = ±1 which have been studied [46,47,48,42]. Further comparative studies of the stochastic resonance for the diffusion case X t versus the Markov Chain Y t case were done by Hermann, Imkeller, Pavlyukevich and Peithmann in [49,50,51,52]. A collection of papers on comparative studies between stochastic resonance in diffusion and Markov Chains can be found in the monograph [42].…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…As mentioned above in leading order the transitions of the diffusion process X t between the wells can be approximated by a two state Markov Chain Y t = ±1 which have been studied [45,46,47,41]. Further comparative studies of the stochastic resonance for the diffusion case X t versus the Markov Chain Y t case were done by Hermann, Imkeller, Pavlyukevich and Peithmann in [48,49,50,51]. A collection of papers on comparative studies between stochastic resonance in diffusion and Markov Chains can be found in the monograph [41].…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…The more realistic second one is given by a conceptual bi-stable diffusion model driven by a Brownian motion with a time-periodic potential function which has two minima the depths of which fluctuate periodically. The noise is implemented with intensities at which the solution trajectories show some random periodicity which can be measured by means of quality of periodic tuning notions (see Herrmann and Imkeller 2003;Herrmann et al 2003;Imkeller and Pavlyukevich 2002).…”
Section: Introductionmentioning
confidence: 99%